The Use of Picture Card Media to Increase Mufrodat at Al-Ghaffar Islamic Elementary School - Jailani, Muhammad; Al Faruqi, Mhd Ibnu Hanan; Ayuni, Rizka Qurrata; Taufiqurrahman, Moh (Abjadia : International Journal of Education, 2025)
Language plays an important role in students' intellectual, social, and emotional development, as well as success in a variety of subjects. Arabic language education in madrassas aims to develop four language skills: listening, speaking, reading, and writing. Mastery of vocabulary (mufrodat) is the key to mastering these skills. Learning media such as flashcards are effective in helping vocabulary teaching. This study aims to describe the use of picture cards to improve mufrodat in SD Islam Al-Ghaffaar. The method used is qualitative descriptive with primary data from students and teachers, as well as secondary data from related literature. Data collection techniques use observation, interviews, and documentation. The results of the study showed that the use of picture cards in mufrodat learning improved students' ability to remember and use Arabic vocabulary. The research stages include preparation (making picture cards), implementation (teaching with a group method), and evaluation (assessment of student understanding). Students show significant improvements in mufrodat mastery and Arabic language skills. In conclusion, the media of picture cards is effective in improving the mufrodat and Arabic language skills of 4th grade students of Al-Ghaffar Islamic Elementary School.